Efeitos agudos de dois protocolos de corrida na função dos músculos do assoalho pélvico feminino - Maniglia, Marcela Camargo Magalhães (2018)
Objectives: To evaluate the presence of urinary incontinence and the function of the pelvic floor muscles of long distance runners, before and immediately after two running situations: race at maximum intensity and submaximal intensity. Methods: A cross-sectional study was performed with 15 nulliparous women who practiced long distance running for at least 12 months and a minimum frequency of 3 times a week. On the first day, the treadmill test was performed, based on an incremental speed protocol, intense and short, and on the second day, the long test, with duration of one hour and average speed, was performed based on the incremental test result. The evaluation of pelvic floor muscles was performed both days before and immediately after the treadmill test using vaginal palpation using the Oxford scale and manometry using Peritron brand device. Results: Fifteen nulliparous women (6 continents (40%) 9 incontinent (60%)) were included in the study. There was no significant difference in the function of the MAP between the groups of continents and incontinetes. Regarding the tests on the treadmill, there was no difference in MAP function before and after application of the two protocols, in the values of Oxford, peak pressure and mean pressure. Conclusion: Running at high and moderate intensity does not seem to affect acutely the function of MAP in long distance corridors.